Congenital transmission of Chagas disease in the Honorio Delgado Arequipa Regional Hospital, Health Center and Regional Hospital La Joya Aplao - Manrique, Miguel (2015)
We studied 220 women in labor and their newborn Regional Hospital Honorio Delgado Arequipa Aplao Hospital and Health Center Jewel. Of these samples, only 212 (... 96.36%) serological tests, complement fixation reaction (RFC) and indirect hemagglutination (Hal) for Chagas disease was performed. A 220 newborns were applied xenodiagnosis. A clinical and epidemiologic profile was used. We think that this exhibition is significant according to deliveries taken during the study period (19.61% Arequipa, La Joya Aplao 53.33% and 43.48%) and because we observed a high percentage of epidemiological history (61.9% parturients were born in endemic area, 69.57% presented background vector Sting). We obtained 6 cases of parturients v 4 newborns serological positive; seroreactivity correlation of the mother / newborn in 4 cases, either the RFC or Hal found. Cases of newborns through xenodiagnosis is not checked, since this reading was negative; we believe that seropositivity is by passage of antibodies.